N. F. S. Grundtvig: Taler på Marienlyst højskole 1856-1871 - Albeck, Gustav (Grundtvig-studier, 1957)
N. F. S. Grundtvig: Adresses Delivered at Marielyst High-School, 1856—1871. Edited by Steen Johansen. Studies Published by the Grundtvig-Society , X. 1956. By Gustav Albeck. On November 3rd, 1856, Grundtvig’s High-School, “ Marielyst”, was opened; it now lives on as “ Grundtvig’s High-School” in Frederiksborg. Its jubilee was celebrated in various ways. The Grundtvig Society’s contribution was of a literary nature, an edition of Grundtvig’s adresses delivered at the school, from the opening day till November 2nd, 1871, when he spoke at the opening of the winter course. The work of editing these adresses has been carried out by Steen Johansen, M. A., who gives a rareful account of his sources and provides in the notes a wealth of useful comments and explanations. Taken as a whole, the little book may appear to be a rather monotonous sermon on the text of Grundtvig’s own making: “ What sunshine is for the dark soil” etc. But if one goes into it more closely one finds in it a wealth of details and definitions which enrich our knowledge of Grundtvig’s views on the true nature of popular education, and give lasting value to the book.